STRATEGI BERTAHAN HIDUP PEMULUNG (Study di Kelurahan Duri Barat Kecamatan Mandau Kabupaten Bengkalis) - Al Kisah, Juliya; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study was analyzed the scavenger about their strategy to survive and their socioecomic with the secondhand warehouse owner in west Duri, Mandau, Bengkalis District. This phenomenon is one of socio phenomenon that happen in the low economic society like the secondhand scavenger in west Duri, Mandau,Bengkalis District. The writer was used surviving strategy, the adaptation of scavenger’s socioeconomic and the relationship about scavenger’s socioeconomic. The data analysis was to answered the problem of this study with the qualititative research, descriptive approach and analyzed by the theories of this research and will presented the narration form by the qualititative away. the data collection technique in this study used purposive sampling that consists of 7 scavenger’s from 2 different secondhand warehouse. based on the result of this research, the scavenger’s used 3 strategic to survive such as applied the active strategic (family abuse), the passive strategic (save the money for their life) and the last is network strategic (estabilished relationships or having good relation among other relations). then, the socioeconomic relationship between the scavengers with the owner of secondhand warehouse could running well.keywords: scavenger, survive, socioeconomic relationship